Dari Lemak ke Sendi: Bahaya Proporsi Lemak Tubuh sebagai Penyebab Osteoartritis Lutut - Kwok, Lyvia Ariella; Kristian, Kevin; Handajani, Yvonne Suzy; Barus, Jimmy Fransisco Abadinta (Jurnal Kedokteran Meditek, 2025)
Introduction: As individuals age, the incidence of osteoarthritis increases. Globally, it is reported that approximately 300 million individuals, particularly the elderly, are affected by osteoarthritis. Metabolic disorders related to lipid pathways have been associated with the development of osteoarthritis in the elderly. Purpose: This study aims to provide an overview of the relationship between haematological indicators, lipid profiles, and body fat proportion with osteoarthritis in the elderly population in Pusaka Kebon Jeruk, West Jakarta. Methods: This study used a cross-sectional design involving an elderly population, with 100 respondents aged ≥60 years who were willing to participate. Data were collected through interviews using an osteoarthritis questionnaire, blood draws, and measurements using BIA. The chi-square test (p<0.05) and multiple logistic regression (p<0.25) were used in this study. Results: Of the 100 respondents, it was found that 28% of the elderly respondents experienced osteoarthritis. Bivariate analysis showed a significant relationship between body fat proportion and osteoarthritis (p: 0.006; OR: 3.519; 95% CI: 1.394–8.878). Multivariate analysis indicated that body fat proportion was the dominant factor associated with osteoarthritis (p: 0.006; OR: 3.814; 95% CI: 1.475–9.865). Conclusions: We concluded that body fat proportion has a significant relationship with the incidence of osteoarthritis. However, this study did not find any significant associations between hemoglobin, white blood cells, RDW, LDL, HDL, triglycerides, and cholesterol.